2018
DOI: 10.22270/jddt.v8i6-s.2229
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical standardization of Hansraj (Adiantum capillus-Veneris)

Abstract: Ethno-botanical use and traditional knowledge of plants have been usually recognized all over the world. The outstanding characteristics of extracts obtained from this drug have been technically studied, attributing the main biological activity to its tannin and flavonoid content. Recent study about this drug Adiantum capillus-veneris Linn requires pharmacognostical evidences to develop quality-control methods for raw materials and extracts produced with this plant drug.  In this research article macro and mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…The repeated administration of doses up to 800 mg/kg to normal rats did not produce observable toxic effects at the doses tested. This is consistent with other reports which showed that mistletoes extracts are relatively non-toxic [30,31,32]. However, in handling the plant material from raw material to extract, physicochemical reference like moisture and ash are critical so as to avoid deterioration, microbial and fungal growth that can be introduced as toxicants [33].…”
Section: However Lymphocyticsupporting
confidence: 91%
“…The repeated administration of doses up to 800 mg/kg to normal rats did not produce observable toxic effects at the doses tested. This is consistent with other reports which showed that mistletoes extracts are relatively non-toxic [30,31,32]. However, in handling the plant material from raw material to extract, physicochemical reference like moisture and ash are critical so as to avoid deterioration, microbial and fungal growth that can be introduced as toxicants [33].…”
Section: However Lymphocyticsupporting
confidence: 91%
“…The components were identified by comparing their retention times and mass spectra to the databases Wiley 09 and NIST 11 [ 121 ]. Assays for the AP moisture content%, pH, cold extract%, hot extract%, ash (total, acid insoluble, and water-soluble ash%), and total phenolic compound% and tests for saponins, tannin, flavonoids, and proteins were performed according to the method described in [ 122 ], as shown in Table 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Whenever the quality assurance entity had also identifying of drug, adulterants, substitutes, and assay of active chemical constituent of greater importance of speci ic plant then they would be termed just like phamacopeial level of quality regulation. It is really is predicted upon that various important analysis parameter such as organoleptic characteristics, residue value, water content, bacterial contamination as well as spectroscopic but also chromatographic evaluation [11,12].…”
Section: Quality Control and Standardization Of Medicinal Herbs And P...mentioning
confidence: 99%